SYSTEMATIC ANALYSIS OF THE SPHERE OF ECONOMIC SECURITY OF UKRAINE IN CONDITIONS OF LIMITED RESOURCES IN THE CONTEXT OF THE POLICY OF SUSTAINABLE DEVELOPMENT - Shevchuk, Inna; Omelchuk, Lesya (Socio-economic relations in the digital society, 2023)
The study noted that new challenges and threats form new requirements for the process of formation and implementation of state policy in the field of economic security in conditions of limited resources in the context of sustainable development of the country, and, accordingly, the category "economic security" is inextricably linked with the categories "competitiveness" and "economic sustainability". It is noted that economic cooperation and economic patronage are the optimal forms of ensuring economic security in a difficult forecast period. It was emphasized that the national economy in today’s conditions needs a certain militarization with the most effective use of international economic aid in the following areas: reconstruction (restoration) of key infrastructure facilities, application of new technologies for the restoration of basic sectors of the national economy, training/hiring of crisis managers and cyber security specialists, etc. In particular, the fragmentation and inconsistency of the state policy in the economic sphere, the lack of a clearly defined road map leads to the distortion of the system of measures for the detinization of economic relations. The author emphasizes that the formation and implementation of the policy of sustainable development both during the war and in the post-war period requires a clearly formed vision of the further development of strategically important sectors of the economy, countering destructive endogenous and exogenous outflows, conducting systematic monitoring of the quality of implementation of the plan of measures of strategic documents in the researched sphere in order to ensure the stability of the economic system, taking into account the change in the paradigm of the study of economic processes. It is summarized that the systematic analysis and assessment of the state of the sphere of economic security of the state serves as the basis of strategic documents for public authorities, however, regulatory support needs to be revised.